Studying the content of phenolic compounds of Bupleurum scorzonerifolium Willd., growing in the Baikal region with HPLC - V. M. Mirovich; S. A. Petukhova; L. V. Dudareva (Acta Biomedica Scientifica)
Phenolic compounds of plants have a wide spectrum of pharmacological action. A number of effective herbal medicines and biologically active additives have been developed on the basis of raw materials and natural polyphenols. The sources of phenolic compounds are plants of the genus Bupleurum L. In Russia Bupleurum scorzonerifolium used in folk medicine. Infusions and decoctions were taken for diseases of the liver, gall bladder, topically as an anti-inflammatory agent. The composition of phenolic compounds in the above-ground organs of the B. scorzonerifolium studied by HPLC on the device "GILSTON". Samples of raw materials (above-ground organs) were collected in the southern areas of the Irkutsk region. For the analysis of the herb B. scorzonerifolium 70% extract ethyl alcohol was used. Separation was performed on substances Kromasil C18 column (4,6 x 250 mm, 5 micron). Detection was carried out using a UV detector "GILSTON" UV/VIS model 151, at a wavelength of 254 nm. In comparison with standard samples we identified 8 flavonoids (prevailing - izoquercetin, hyperoside, izoramnetin-3-glucoside), 5 aromatic acids (predominantly acid - cinnamic, gallic, chicory). The study established the content of epicatechin, catechin, epigallocatechingallate, coumarin. For the first time the content of acids - coffee, chlorogenic, gallic, chicory, cinnamon; flavonoids - vitsenin, lyuteolin-7-glucoside, isoramnetin-3-glucoside, apigenin; epicatechin, catechin, epigallocatechingallate; coumarin -was established in B. scorzonerifolium.